2010
DOI: 10.1212/wnl.0b013e3181d5279e
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E neuroprotection for cisplatin neuropathy

Abstract: This study provides Class II evidence that vitamin E supplementation significantly reduces the relative risk of developing signs or symptoms of neurotoxicity (relative risk = 0.14) (95% confidence interval = 0.02-1.00, p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
1
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 24 publications
(28 reference statements)
2
109
1
7
Order By: Relevance
“…Recently, a neuroprotective effect of vitamin E against CIPN has been reported. 33 Pharmacologic studies are necessary to determine dose and duration of ATRA therapy in CIPN. We selected the doses used in this study based on previous experimental reports on tolerance.…”
Section: Statistical Analysis Continuous Variables Were Summarized Asmentioning
confidence: 99%
“…Recently, a neuroprotective effect of vitamin E against CIPN has been reported. 33 Pharmacologic studies are necessary to determine dose and duration of ATRA therapy in CIPN. We selected the doses used in this study based on previous experimental reports on tolerance.…”
Section: Statistical Analysis Continuous Variables Were Summarized Asmentioning
confidence: 99%
“…The severity of neurotoxicity, measured with a comprehensive neurotoxicity score based on clinical and neurophysiological parameters, was significantly lower in patients of the vitamin E group than in patients in the control group (2 versus 4.7) (Pace et al, 2003). Later, Pace and colleagues performed a 2 center, double-blind, randomized, placebo controlled study of cisplatin induced neuropathy in solid tumor patients (Pace et al, 2010). A total of 108 patients treated with cisplatin chemotherapy were randomly assigned to receive vitamin E (400 mg/day) or placebo orally.…”
Section: Vitamin Ementioning
confidence: 99%
“…Neurotoxicity was measured with Total Neuropathy Score, and revealed a mean score of 1.4 in the vitamin E group versus 4.1 in the placebo group (p < 0.01). On sensory nerve conduction study, mean sural and median sensory amplitudes were both significantly reduced in the control group, while only mildly reduced in the sural nerve and unchanged in the median nerve in the vitamin E group (Pace et al, 2010). Argyriou and colleagues conducted 3 randomized, open label with blind assessment, controlled trials to determine whether vitamin E has a neuroprotective effect in chemotherapyinduced peripheral nerve damage.…”
Section: Vitamin Ementioning
confidence: 99%
“…Although normal pain relief does not reduce the pain associated with CIPN, no specific anti-inflammatory drug has been trialled as a protective agent. This is one of the main mechanisms of action that has been identified in the nutrients and the herbs trialled for CIPN that have shown a possible beneficial protective effect [233][234][235][236][237][238][239][240][241][242][243][244][245][246]. The anti-inflammatory component may or may not protect patients against CIPN but it would be an interesting aspect to investigate.…”
Section: Strengths and Weaknesses And Gaps In The Researchmentioning
confidence: 99%
“…Vitamin E was demonstrated to have positive results in three RCT's showing a significant reduction in the relative risk of cisplatin induced PN, especially ototoxicity [233][234][235][236]254]. However, a phase III multi-centre trial combining vitamin E with taxanes, cisplatin, carboplatin, oxaliplatin or combination concluded that vitamin E did not appear to reduce the incidence of sensory neuropathy [254].…”
Section: Vitamin Ementioning
confidence: 99%